Optical Link Fault Detection and Localization in Passive Optical Network Domain - Nadiatulhuda Zulkifli , Auwalu Usman , Mohd Rashidi Bn Salim , Kharina Khairi (International Journal of Advanced Science and Technology, 2020)
Optical link fault detection and localization are significant in the Passive optical network (PON) due to the passive nature of the network elements involved. A single failure in the optical link can resort to a huge amount of data loss in the network. However, deployment of fault detection and localization devices is extremely limited due to the extra cost network operators need to pay and the reliability of the devices. PON fault monitoring solutions have been investigated by the researchers over the decades; the challenges for these monitoring techniques are the cost and complexity of their deployment. Thus, this work proposes a technique for the detection and localization of fault in the optical link of a PON Fiber-to-the-x (FTTx) network using optical reflectors. The real-time back-reflected signal from the reflectors in the network will be utilized to determine the optical link with fault. Experimental results obtained show that multiple optical link impairments can be detected and localized in the PON FTTx based network in-service, over a distance of 20 km, in a cost-effective manner. Measurements from a standard Optical Time-Domain Reflectometer (OTDR) is used to prove the validity of our technique